The costs of ambiguity in strategic contexts - Richard J. Arend (Administrative Sciences, 2022)
With this research, we contribute to the study of ambiguity by analyzing how it can be handled in a rational, objective manner across the main strategic decision-making contexts that entrepreneurs and organizations face. Differentiating from most previous managerial and entrepreneurial studies, we conduct the analysis from a mathematical rather than an experimental approach, doing so by considering variants of a robust, yet simple, decision problem. Significantly, the analysis offers a simple model and approach to consider as benchmarks when assessing the impact of an ambiguity level of information against cases where more precise information is available. We identify the many costs of ambiguity, including direct absolute and relative maximum harms, as well as indirect possible penalties. We discuss the strategic entrepreneurial and managerial implications.
Keywords: 350; ambiguity; decision-making; optimization; risk; uncertainty; value of information